2008
DOI: 10.1121/1.2933804
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic analysis of the vocal tract during vowel production by finite-difference time-domain method

Abstract: An acoustic simulator based on the finite-difference time-domain (FDTD) method was evaluated by acoustic measurements on solid models of the vocal tract. Three-dimensional vocal tract (3D VT) shapes for a male subject during production of the five Japanese vowels were measured by magnetic resonance imaging. Transfer functions of the 3D VT shapes were computed by the acoustic simulator. The accuracy of the finite-difference algorithm was second-order in time and fourth-order in space. From the same 3D VT shapes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
70
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(76 citation statements)
references
References 0 publications
4
70
0
2
Order By: Relevance
“…2 with area functions). The pole/zero pair at approximately 3,300 Hz can be ascribed to an interdental space [18]. The formant at approximately 4,400 Hz is probably an oral formant shifted by the presence of a pole/ zero pair at approximately 4,700 Hz owing to the piriform sinuses, which are not modeled for the French subject.…”
Section: Discussionmentioning
confidence: 99%
“…2 with area functions). The pole/zero pair at approximately 3,300 Hz can be ascribed to an interdental space [18]. The formant at approximately 4,400 Hz is probably an oral formant shifted by the presence of a pole/ zero pair at approximately 4,700 Hz owing to the piriform sinuses, which are not modeled for the French subject.…”
Section: Discussionmentioning
confidence: 99%
“…Dang and Honda reported that the piriform fossa contributes strong troughs to the VTTFs, as determined from measurement experiments using an MRIbased mechanical model [2]. Takemoto et al reported the acoustical effects of the piriform fossae, epiglottic valleculae, and interdental spaces determined from measurement experiments and computer simulation using MRI-based physical models and finite-difference time-domain analysis data [3]. However, when the model is geometrically smoothed, the extra poles and zeros sometimes disappear in the VTTFs.…”
Section: Introductionmentioning
confidence: 99%
“…The latter boundary condition does not consider radiation losses. These could be implemented by extending the computational domain outside the vocal tract [20,21], but at the prize of increasing the computational cost. The sequence [Ai] was generated by numerically solving the ALE mixed wave equation (1) with boundary and initial conditions (2) using the Finite Element Method (FEM).…”
Section: Acoustic Modelmentioning
confidence: 99%